Characterization of exhaled particle deposition and ventilation in an indoor setting. (1st October 2021) - Eilts, Stephanie M.; Li, Linhao; Pope, Zachary C.; Hogan, Christopher J.
Abstract: Exhalation of infectious micrometer-sized particles has been strongly implicated in respiratory infection spread. An important fundamental question is then the fate of infectious exhaled particles in indoor spaces, i.e., whether they will remain suspended in an aerosol until ventilation leads to their clearance or whether they will deposit, and if so, on what surfaces in an indoor space. We investigated the interplay between deposition and ventilation using model experiments with a breathing simulator manikin in an office environment. The breathing simulator utilized physiologically correct exhalation and inhalation breathing waveforms as well as an anatomically correct manikin. The simulator output fluorescein-doped particles with a volume distribution spanning the 1–3 μm range. The office environment was a 344 m 3 room equipped with desks. Four different test conditions were created by changing the simulator location and via different air change rates and MERV ratings of filters in the HVAC system. We found that the rate of ventilation exceeds the rate of deposition on all surfaces (quantified by Stanton numbers, which were below unity) with several important exceptions: (1) surfaces close to (within 2 m of) the simulator; and (2) non-passive surface exteriors (return grilles and diffusers). A detectable decrease in Stanton number with distance suggests that the room environment cannot be approximated as truly well-mixed. The finding of enhanced deposition on non-passive surfaces at all distances from the room highlights that infectious particles may preferentially deposit on such surfaces in indoor spaces. Finally, while our results highlight particular surfaces with enhanced deposition, our results confirm the importance of ventilation in a room as a means to reduce infectious aerosol particle concentrations, as in large part the clearance for particles appears to occur by ventilation. Highlights: Deposition was observed through the use of a breathing simulator which output fluorescein particles. The rate of deposition vs ventilation was investigated through the use of a Stanton number. Enhanced deposition of particles was observed near the breathing simulator.